Environmental protection tax, corporate ESG performance, and green technological innovation - Li, Jing; Li, Shiyu (Frontiers in Environmental Science, 2022)
Environmental, social, and corporate governance (ESG) performance is an analytical framework for measuring the contribution of enterprises to sustainable development and fulfillment of social responsibility. The introduction of an environmental protection tax in China in 2018, which imposes tax on the pollution emission of enterprises, helps enterprises improve their ESG performance and raise their environmental awareness, thus effectively promoting their green technological innovation to achieve sustainable development. This study examines the effect of China’s environmental protection tax on corporate ESG performance and green technology innovation. The findings showed that the environmental protection tax in China can vastly improve the ESG performance and green technological innovation, with the ESG performance exhibiting a partial mediating effect in promoting corporate green technological innovation. The mediating effect in enhancing ESG performance and green technological innovation varies with the nature of firms’ property rights and regions.